Despite High Local Knowledge, Limited Stakeholder Participation and Resource Mobilization Constrain the Effective Management of Invasive Plants in Nepal’s Protected Areas - Junusha Poudel; Tulasa Chaudhary; Uttam Babu Shrestha; Ross T. Shackleton; Bharat Babu Shrestha (Environmental Management, 2026)

Abandoned fields show higher insectivorous Bat species and functional diversity than forest fragments in a communal land area of the Eastern Cape, South Africa - Khia R. van der Meulen; Leigh R. Richards; Ross T. Shackleton; Michael I. Cherry (Biodiversity and Conservation, 2025)
Deagrarianisation is a global phenomenon with high potential for both carbon sequestration and biodiversity conservation. Work on this topic has focused on plant succession and associated plant diversity, but few studies have considered faunal communities, particularly in Africa. We used passive acoustic monitoring to record insectivorous bat communities within forest fragments and former fields under communal land tenure in the Transkei region (Eastern Cape Province) of South Africa. Insectivorous bat diversity in fields, abandoned in the 1960s to 1980s, resembling late stages of succession, were compared to fragments of Transkei Coastal Scarp Forest embedded within the landscape. We found that former fields hosted 14 species from 11 genera, comprising greater species richness, activity, Shannon-Weiner diversity, and functional diversity, irrespective of age, compared to forest fragments, which hosted nine species from seven genera. Furthermore, former fields exhibited comparable species richness to, and higher functional diversity than, three large neighbouring intact Transkei Scarp forests. Interestingly, the time since cultivation had ceased (35—64 years ago) had no significant effect on species and functional diversity. Former fields exhibited extensive invasion by Lantana camara (an alien shrub), and the indigenous pioneer tree Vachellia karoo , but nonetheless these landscapes have conservation value as they are diverse in both terms of insectivorous bat species and function. Mechanisms to enhance both biodiversity conservation; and the utility of the land for impoverished local communities, should be considered for former fields in tandem with forest patches, which remain important for bat roosting and foraging ecology, especially for specialist species.

Effects of conspecific and congeneric soils and litters on the nodulation and growth of non-native invasive and native Prosopis species in arid deserts - Ali El-Keblawy; Elsiddig A.E. Elsheikh; Ana Novoa; Ross T. Shackleton; Mohamed Sheteiwy; Salma K. Shaltout (Journal of Arid Environments, 2025)

Gauging the threat of invasive species to UNESCO world heritage sites relative to other anthropogenic threats - Marc William Cadotte; Mohamed Alabbasi; Sara Akib; Pruthuvie Chandradhas; Joanne Gui; Kelly Huang; Adrian Li; David M. Richardson; Ross T. Shackleton (Biological Invasions, 2024)

The impact of the invasive alien plant Vernonanthura polyanthes on conservation and livelihoods in the Chimanimani uplands of Zimbabwe - Lameck Kachena; Ross T. Shackleton (Biological Invasions, 2024)
Biological invasions can have major social-ecological consequences for rural communities across the world. However, the dimensions (characteristics, infestation and socio-ecological impacts) of emerging invasive alien plants are often less known and urgent information is needed to guide policy and management. In light of this, this paper assesses the social-ecological impacts of Vernonanthura polyanthes, an emerging invasive alien plant found in a Zimbabwean upland landscape which supports conservation and livelihoods. The paper employs qualitative methods—community mapping, time series analysis, and key informant interviews—involving individuals from diverse socio-economic backgrounds, to examine the socio-ecological and economic implications of V. polyanthes and its management in Chimanimani, Zimbabwe. We found that there are nuanced perspectives regarding this invasive alien plant among different socio-economic groups in the region who have different experiences of living with V. polyanthes . Some are embracing it for apiculture, firewood, and ethnomedicine while, on the other hand, some see the tree as negatively affecting key livelihoods (crop farming, pastoralism, and tourism) that are common in the region. Local people also identified that V. polyanthes is associated with ecological impacts that include loss of biodiversity, promoting pests, and negatively affecting watersheds and associated water sources. These mixed experiences concerning the plant are leading to different management practices, in turn inducing some conflicts among various actors. Based on our findings, we suggest more should be done to better manage this invasive alien plant in the region before negative impacts become too great, particularly in protected areas.

No evidence that coring affects tree growth or mortality in three common European temperate forest tree species - Jeanne Portier; Ross T. Shackleton; Stefan Klesse; Marco Ferretti; Roman Flury; Martina L. Hobi; Jonas Stillhard; Georg von Arx; Brigitte Rohner; Esther Thürig (European Journal of Forest Research, 2024)
Tree cores are a highly valuable scientific resource. Annual growth ring data can, for example, improve our understanding of climate change impacts and effects of environmental pollution, allow for better annual estimations of tree growth patterns and carbon storage, and help quantify dynamics and changes in forest ecosystems. The value of coring trees for research has been weighted against concerns around the potential harm coring might cause to trees. To date, there is indeed limited research accurately quantifying the potential effects of coring on tree growth and only a handful of studies assessing its influence on mortality. Consequently, many European long-term forest inventorying and monitoring programs are concerned that tree coring might bias the repeated tree measurements in permanent plots, which they rely on for assessments of states and changes of forests. In this study, we assessed the effects of tree coring on the growth and mortality of three widespread European tree species approximately 10 years after they were cored. We used repeated tree measurements from permanent research sites in Switzerland and Ukraine. In Switzerland, we assessed 35 cored and 159 uncored Norway spruce ( Picea abies ) trees as well as 147 cored and 332 uncored silver fir ( Abies alba ) trees. In Ukraine, we assessed 348 cored and 6′611 uncored European beech ( Fagus sylvatica ) trees. We found no statistical evidence that coring negatively affected the growth or mortality of the three tree species assessed. Although we cannot rule out subtle effects on tree health and wood quality, our findings do not provide any evidence that coring affects or biases repeated measurements (such as DBH measures and recording of mortality) performed on the investigated tree species. Tree coring could therefore be considered more often for routine incorporation, particularly in long-term forest inventorying and monitoring programs and initiatives.

Consensus and controversy in the discipline of invasion science - Ross T. Shackleton; Giovanni Vimercati; Anna F. Probert; Sven Bacher; Christian A. Kull; Ana Novoa (Conservation Biology, 2022)
Approaches, values, and perceptions in invasion science are highly dynamic, and like in other disciplines, views among different people can diverge. This has led to debate in the field specifically surrounding the core themes of values, management, impacts, and terminology. Considering these debates, we surveyed 698 scientists and practitioners globally to assess levels of polarization (opposing views) on core and contentious topics. The survey was distributed online (via Google Forms) and promoted through listservs and social media. Although there were generally high levels of consensus among respondents, there was some polarization (scores of ≥0.39 [top quartile]). Relating to values, there was high polarization regarding claims of invasive species denialism, whether invasive species contribute to biodiversity, and how biodiversity reporting should be conducted. With regard to management, there were polarized views on banning the commercial use of beneficial invasive species, the extent to which stakeholders’ perceptions should influence management, whether invasive species use alone is an appropriate control strategy, and whether eradication of invasive plants is possible. For impacts, there was high polarization concerning whether invasive species drive or are a side effect of degradation and whether invasive species benefits are understated. For terminology, polarized views related to defining invasive species based only on spread, whether species can be labeled as invasive in their native ranges, and whether language used is too xenophobic. Factor and regression analysis revealed that views were particularly divergent between people working on different invasive taxa (plants and mammals) and in different disciplines (between biologists and social scientists), between academics and practitioners, and between world regions (between Africa and the Global North). Unlike in other studies, age and gender had a limited influence on response patterns. Better integration globally and between disciplines, taxa, and sectors (e.g., academic vs. practitioners) could help build broader understanding and consensus.

Biological invasions in World Heritage Sites: current status and a proposed monitoring and reporting framework - Ross T. Shackleton; Bastian Bertzky; Louisa E. Wood; Nancy Bunbury; Heinke Jäger; Remco van Merm; Christian Sevilla; Kevin Smith; John R. U. Wilson; Arne B. R. Witt; David M. Richardson (Biodiversity and Conservation, 2020)
UNESCO World Heritage Sites (WHS) are areas of outstanding universal value and conservation importance. They are, however, threatened by a variety of global change drivers, including biological invasions. We assessed the current status of biological invasions and their management in 241 natural and mixed WHS globally by reviewing documents collated by UNESCO and IUCN. We found that reports on the status of biological invasions in WHS were often irregular or inconsistent. Therefore, while some reports were very informative, they were hard to compare because no systematic method of reporting was followed. Our review revealed that almost 300 different invasive alien species (IAS) were considered as a threat to just over half of all WHS. Information on IAS management undertaken in WHS was available for fewer than half of the sites that listed IAS as a threat. There is clearly a need for an improved monitoring and reporting system for biological invasions in WHS and likely the same for other protected areas globally. To address this issue, we developed a new framework to guide monitoring and reporting of IAS in protected areas building on globally accepted standards for IAS assessments, and tested it on seven WHS. The framework requires the collation of information and reporting on pathways, alien species presence, impacts, and management, the estimation of future threats and management needs, assessments of knowledge and gaps, and, using all of this information allows for an overall threat score to be assigned to the protected area. This new framework should help to improve monitoring of IAS in protected areas moving forward.

Integrated Methods for Monitoring the Invasive Potential and Management of Heracleum mantegazzianum (giant hogweed) in Switzerland - Ross T. Shackleton; Blaise Petitpierre; Mila Pajkovic; Florian Dessimoz; Olivier Brönnimann; Loïc Cattin; Šárka Čejková; Christian A. Kull; Jan Pergl; Petr Pyšek; Nigel Yoccoz; Antoine Guisan (Environmental Management, 2020)

Invasion syndromes: a systematic approach for predicting biological invasions and facilitating effective management - Ana Novoa; David M. Richardson; Petr Pyšek; Laura A. Meyerson; Sven Bacher; Susan Canavan; Jane A. Catford; Jan Čuda; Franz Essl; Llewellyn C. Foxcroft; Piero Genovesi; Heidi Hirsch; et al. (Biological Invasions, 2020)
Our ability to predict invasions has been hindered by the seemingly idiosyncratic context-dependency of individual invasions. However, we argue that robust and useful generalisations in invasion science can be made by considering “invasion syndromes” which we define as “a combination of pathways, alien species traits, and characteristics of the recipient ecosystem which collectively result in predictable dynamics and impacts, and that can be managed effectively using specific policy and management actions”. We describe this approach and outline examples that highlight its utility, including: cacti with clonal fragmentation in arid ecosystems; small aquatic organisms introduced through ballast water in harbours; large ranid frogs with frequent secondary transfers; piscivorous freshwater fishes in connected aquatic ecosystems; plant invasions in high-elevation areas; tall-statured grasses; and tree-feeding insects in forests with suitable hosts. We propose a systematic method for identifying and delimiting invasion syndromes. We argue that invasion syndromes can account for the context-dependency of biological invasions while incorporating insights from comparative studies. Adopting this approach will help to structure thinking, identify transferrable risk assessment and management lessons, and highlight similarities among events that were previously considered disparate invasion phenomena.

The impact of invasive aquatic plants on ecosystem services and human well-being in Wular Lake, India - Reuben P. Keller; Ather Masoodi; Ross T. Shackleton (Regional Environmental Change, 2018)

Distribution and socio-ecological impacts of the invasive alien cactus Opuntia stricta in eastern Africa - Ross T. Shackleton; Arne B. R. Witt; Francis M. Piroris; Brian W. van Wilgen (Biological Invasions, 2017)

Chromolaena odorata (Siam weed) in eastern Africa: distribution and socio-ecological impacts - Ross T. Shackleton; Arne B. R. Witt; Winnie Nunda; David M. Richardson (Biological Invasions, 2017)

Stakeholder perceptions and practices regarding Prosopis (mesquite) invasions and management in South Africa - Ross T. Shackleton; David C. Le Maitre; David M. Richardson (Ambio, 2015)